2018
DOI: 10.1096/fj.201701069r
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetyltransferase CBP promotes function of SCF FBXL19 ubiquitin E3 ligase by acetylation and stabilization of its F‐box protein subunit

Abstract: Ubiquitin E3 ligases mediate ubiquitination and degradation of intracellular proteins. We have shown that a relatively new Skp, Cullin, F-box (SCF) protein E3 ligase, SCF FBXL19, has an anti-inflammatory effect and controls actin cytoskeleton dynamics via targeting cell membrane receptor and small GTPases for their ubiquitination and degradation, but the molecular regulation of its subunit FBXL19 stability remains unclear. Here we show that FBXL19 degradation is controlled by the balance between its ubiquitina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 30 publications
2
22
1
Order By: Relevance
“…Since nonhistone acetylation was first identified, increasingly more functions for acetylation have been found to act on various life processes, including DNA damage response and autophagy (Botrugno et al, 2012;Zhong et al, 2017;Yasuda et al, 2018), genomic stability (Billon et al, 2017;Fournier and Tora, 2017), transcriptional activity (Seo et al, 2015), protein degradation (Liu et al, 2013;Wei et al, 2018) and lysosomal function (Zhang et al, 2018). Previous studies have shown that acetylation could compete with ubiquitination at the same lysine residue, thus blocking the ubiquitin-mediated proteasomal degradation pathway to improve the protein stability, which is involved in cell cycle regulation (Lahusen et al, 2018), tumour suppression and progression (Wan et al, 2015;Choi et al, 2017), bacterial virulence (Sang et al, 2017) and signal transduction (Garcia-Aguilar et al, 2016;Beckwith et al, 2018;Wei et al, 2018). In our previous work, many acetylated sites were found on the nutrient storage proteins in the haemolymph of B. mori, including three storage proteins (SP1, SP2 and SP3), three apolipophorin proteins (BmApoLp-I, BmApoLp-II and BmApoLp-III) and six 30 K proteins (Nie et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Since nonhistone acetylation was first identified, increasingly more functions for acetylation have been found to act on various life processes, including DNA damage response and autophagy (Botrugno et al, 2012;Zhong et al, 2017;Yasuda et al, 2018), genomic stability (Billon et al, 2017;Fournier and Tora, 2017), transcriptional activity (Seo et al, 2015), protein degradation (Liu et al, 2013;Wei et al, 2018) and lysosomal function (Zhang et al, 2018). Previous studies have shown that acetylation could compete with ubiquitination at the same lysine residue, thus blocking the ubiquitin-mediated proteasomal degradation pathway to improve the protein stability, which is involved in cell cycle regulation (Lahusen et al, 2018), tumour suppression and progression (Wan et al, 2015;Choi et al, 2017), bacterial virulence (Sang et al, 2017) and signal transduction (Garcia-Aguilar et al, 2016;Beckwith et al, 2018;Wei et al, 2018). In our previous work, many acetylated sites were found on the nutrient storage proteins in the haemolymph of B. mori, including three storage proteins (SP1, SP2 and SP3), three apolipophorin proteins (BmApoLp-I, BmApoLp-II and BmApoLp-III) and six 30 K proteins (Nie et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…FBXL19, a component of the SCF E3 ligase complex, can specifically recognize substrates for ubiquitination. We have demonstrated that FBXL19 exhibited antiinflammatory properties (33,35) and modulated small G protein stability (32,34,36). In this study, we showed that TTF1 is a new target of FBXL19 in FTC133 cells.…”
Section: Discussionmentioning
confidence: 64%
“…We have demonstrated that FBXL19 regulates IL-33 signaling by targeting its cognate receptor ST2L for ubiquitination (33). In addition to ST2L, we also found that CREB-binding protein (CBP), Rac family small GTPase 1 (Rac1), Rac family small GTPase 1 (Rac3) and Ras homolog gene family, member A (RhoA) are targets for FBXL19 (32,(34)(35)(36). Here, we verified TTF1 as a new target for FBXL19 in follicular thyroid carcinoma.…”
mentioning
confidence: 60%
“…Recent studies have shown that the acetylation of many nonhistone proteins is associated with tumorigenesis, cancer cell proliferation, and immune function, which makes the regulation of protein acetylation a potential approach for the treatment of cancer (de Almeida Nagata et al, ; Dou, Zheng, Liu, & Tu, ; Liu, Li, Wu, & Cho, ). At present, acetylation has been shown to be involved in many important biological processes, including cell apoptosis (Cohen et al, ; S. S. Choi, Rhee, & Park, ), subcellular localization (Fujita, Fujiwara, Zenitani, & Yamashita, ; Ishfaq et al, ; Ito et al, ), DNA replication and repair (Al Emam, Arbon, Jeeves, & Kysela, ; Ghosh, Bohr, & Karmakar, ), DNA and protein interactions (Ugrinova, Pashev, & Pasheva, ), DNA transcription (Asano, Czuwara, & Trojanowska, ), protein stability (J. R. Choi, Lee, Shin, Choi, & Kang, ; J. Y. Choi, Ko, & Jo, ; Ge, Jin, Zhang, Yan, & Zhai, ; Wei et al, ), and so on. Regarding the regulation of protein stability, acetylation can compete with lysine ubiquitination and inhibit the proteasome degradation pathway mediated by ubiquitin, improving the stability and accumulation of proteins in cells that are involved in many physiological functions such as synaptic plasticity and cognitive function (G. Wang et al, ), tumor suppression (J. R. Choi et al, ), nuclear translocation, and transcriptional activity (Ge et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…S. Choi, Rhee, & Park, 2002), subcellular localization (Fujita, Fujiwara, Zenitani, & Yamashita, 2015;Ishfaq et al, 2012;Ito et al, 2015), DNA replication and repair (Al Emam, Arbon, Jeeves, & Kysela, 2018;Ghosh, Bohr, & Karmakar, 2019), DNA and protein interactions (Ugrinova, Pashev, & Pasheva, 2009), DNA transcription (Asano, Czuwara, & Trojanowska, 2007), protein stability (J. R. Choi, Lee, Shin, Choi, & Kang, 2017;J. Y. Choi, Ko, & Jo, 2018;Ge, Jin, Zhang, Yan, & Zhai, 2009;Wei et al, 2018), and so on. Regarding the regulation of protein stability, acetylation can compete with lysine ubiquitination and inhibit the proteasome degradation pathway mediated by ubiquitin, improving the stability and accumulation of proteins in cells that are involved in many physiological functions such as synaptic plasticity and cognitive function (G. Wang et al, 2017), tumor suppression (J. R. Choi et al, 2017), nuclear translocation, and transcriptional activity (Ge et al, 2009).…”
Section: Introductionmentioning
confidence: 99%